Out of equilibrium - Amendola, Mario; Gaffard, Jean-Luc.; Oxford eBooks (Oxford : Clarendon, 1998)
Standard equilibrium economic models focus on interdependencies. This text develops a theory which is based on disequilibria. The model proposed is a heuristic tool that makes it possible to explore these disequilibria in relation to Western economies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Equilibrium (Economics); Electronic books